Clinical trial sith SQ 11, 302 on acute gastroenteritis - J. Mangiwa; Suharti Agusman; Sri Sudarjati Nasar (Indonesian Pediatric Society, 1973)
SQ 11,302, now known as Dexacillin or Epicillin is a new semisynthetic penicillin developed by The Squibb Institute for Medical Research. It is designated chemically as 6-D-2-amino-2- (1,4-cyclohexadien-1-yl) acetamido penicillanic acid.